An Article Of Role Of Matra Basti In Ksheeena Shukra (Journal of Pharmaceutical Negative Results, 2022)
Ksheena Shukra is a disease in which depletion of Shukra is observed both Qualitatively and quantitatively, the ultimate result of thisbeing loss of parenthood. The above picture of the disease holds well even today in Oligospermia, where in there will be decreasedsperm count and which is the major cause for Infertility. Male infertility can arise from factors such as low sperm count and spermabnormalities including altered morphology and low motility. Up to 10% of infertility cannot be explained medically. The term Shukramentioned in our classics has got a wider concept i.e. it includes both endocrine and reproductive functions (Androgen and Semen). Itis very difficult to diagnose Ksheena Shukra with the help of signs and symptoms mentioned in our classics because it was observed inthe study that most of the patients did not have those symptoms. So as the technology is so much advanced, Semen analysis is animportant and necessary investigation to diagnose Oligospermia.Shamana and Shodhana are the two basic principle of Ayurved chikitsa for Ksheena Shukra. In shodhana chikitsa Basti karma isconsidered as the best treatment for Shukra dosha. Acharya Charaka has emphasizes on Basti karma in Ksheena Shukra managenent.Bastikarma is pradhanakarma which is mentioned as Ardhachikitsa, Matrabasti is a type of Anuvasanabasti having wide indications.Matrabasti is a type of Anuvasana which is having main ingredient sneha which is administered in the hraswamatra1. It is well toleratedby the patients because of its dose, neither any complication nor any time restriction is there for administering Matrabasti. KsheenaShukra is most common disease among the infertility patients encountered in clinical practice. It can be compared with Oligospermiaof contemporary science as both are similar in presentation with the symptometology- Low sperm count, low motility and testicularpain etc.